(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
A language mirrors the specific culture of its nation, especially, aphorisms’ role in reflecting national features and culture of this nation is extensive. Traditions of people and culture peculiarities are expressed in aphorisms.